HUMAN–COMPUTER INTERACTION MODELS IN ART PEDAGOGY - Malhotra, Abhiraj; Sharma, Divya; Kuppuswamy, Kishore; Khan, Akhilesh Kumar; Behera, Bhagyalaxmi; Sutaria, Kamal; Deshpande, Leena (ShodhKosh: Journal of Visual and Performing Arts, 2025)
Incorporation of the Human-Computer Interaction (HCI) models in the art pedagogy has changed the way learners interact with the digital creativity with the focus on the interactive, experiential and multimodal approaches to the artistic education. This paper discusses the role of cognitive and behavioral modeling in the HCI models in improving the digital art learning conditions using adaptive and feedback-based systems. The study is based on the theories of constructivist and experiential learning, investigating how creativity and self-expression can be supported by the direct manipulation interface, immersive platform, and generative AI tools. The methodology is a combination of both qualitative and quantitative data gathered through observations in the classroom, surveys, and interviews with the art educator and students in the use of digital art software and interactive learning systems. The measurement of interaction patterns, engagement rates, and learning outcomes are measured by analytical methods in order to determine the pedagogic importance of interface design and multimodal feedback. The results show that properly developed HCI systems have a positive influence on engagement, experimentation, and increase the confidence of students in their creativity. In addition, multimodal interfaces with visual, auditory, and touch-hearing aspects help to build deeper cognitive associations, which lead to better conceptual knowledge and aesthetic decision-making. The discussion indicates the necessity of adaptive digital tools, inclusive, and contextual, which are compatible with the artistic cognition. This study is part of the new body of art-oriented HCI, which promotes an educational model in which interactivity is the medium of creativity, as well as an agent of learning, and the future of online art education.